REPRESENTASI FEMINISME DALAM LAGU K-POP “NXDE” OLEH (G)-IDLE - Tasya Febrianty (Universitas Pembangunan Nasional “Veteran” Jawa Timur, 2000)
Abstract This article examines the representation of feminism in the K-Pop song